(untitled) (Research, Society and Development, 2021)
Introduction: obesity, a chronic non-communicable disease (NCD), considered the most important nutritional disorder in developing and developed countries, due to its increased incidence, is a pathology that is often associated due to its high risk factor, to the possibility of corroborating other metabolic and systemic comorbidities, such as primary hypertension, diabetes mellitus and hypothyroidism. Objective: to relate obesity to other comorbidities, as well as the cost of this disease for public health in Brazil. Methodology: this is a brief literature review. The research was carried out through online access in the National Library of Medicine (PubMed MEDLINE), Scientific Electronic Library Online (Scielo), Google Scholar, Virtual Health Library (VHL) and EBSCO Information Services databases, from April to June of 2021. Results: chronic conditions such as kidney disease, osteoarthritis, cancer, type 2 diabetes mellitus, sleep apnea, non-alcoholic fatty liver disease, systolic arterial hypertension (SAH) and, most importantly, coronary artery disease, are directly related with functional disability and obesity Conclusion: it is well known that the pathophysiology of obesity corroborates later comorbidities, such as SAH, diabetes mellitus, thyroid disorders and dyslipidemia. Allied to this, CNCDs represent a great burden for the public health system in Brazil, given that they are one of the main causes of death and illness in the population, and, in this sense, due to their direct negative effects on health, added to the indirect effects resulting from associated chronic diseases, obesity represents a double burden on health systems.